Police administration towards a vision of public administration (2015)
The present study aims to publicize the importance of the Public Administration covers management of all types of organizations. In this case the National Police, a legendary and hierarchical institution that refuses to abandon its institutional doctrine, but that requires for its operation, observe all the guidelines required by the regulation of the civil service. This is not to challenge the military model that characterizes it comes to assimilate this model to new global trends required by organizations or existing economic blocs, not only is responsible to the state as such, but also to each of the entities They conform. Good allocation of responsibilities to qualified staff is key to institutional success, make the professionalization that currently have a select group of officials towards the pursuit of success of the institution and the same state. The global context requires societies and cultures adapting to a new reality emerging paradigms, which leads to the emergence of new crimes and clashes, which obliges the National Police of Colombia opting for a new trend, not only administrative, but also strategic in their constitutional right.